EVALUATION OF THE ONLINE PASSPORT QUEUE REGISTRATION APPLICATION SYSTEM REGARDING PASSPORT APPLICANT DATA ENTRY MATTERS - Mila Rosmaya; Wisnu Widayat; Fadel Achmad Amril (Polteknik Imigrasi, 2021)
This research discusses about upgrading Aplikasi Pendaftaran Antrian Paspor Online (APAPO) and take an example at South Jakarta Immigration Office. The problems discussed are regarding APAPO who has not yet been optimized, it caused APAPO is not integrated on the system of SPRI application in every immigration office. Ought to the presence of APAPO it can be helpful for immigration officer to providing service. The purposes of this research are to know the workflow of system in the APAPO currently and find the best way to efficiencies of immigration officer in doing the service for the applicant passport in the immigration office. The research is classified qualitative by analizing problems using PDCA theory which includes, Plan, Do, Check, and Action. The results of this research are proven that APAPO has still not been integrated with the system of SPRI application in every immigration office. Therefore, to efficiency immigration officer in order to give a service author provide a recommendation in the form of data flow diagram for upgrading moreover to integration between APAPO and SPRI application with webservice method.